Assessment of intake of calcium and vitamin D and sun exposure in the context of osteoporosis risk in a study conducted on perimenopausal women - Kopiczko, Anna (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: The results of many epidemiological and clinical studies have shown that osteoporosis is a multifactorial disease and develops mainly in women during menopause. The aim of this study was to evaluate the diet with particular emphasis on calcium and vitamin D intake and sun exposure in premenopausal women in terms of risk of osteoporosis. Material and methods : The study involved 300 women aged 45-55 years from Warsaw. The method used was a questionnaire assessing the frequency of consumption from the last three months. Exposure to the sun evaluated using a questionnaire prepared in cooperation with the Institute of Food and Nutrition in Warsaw. For the purpose of the project, profiles of attitudes towards prevention of osteoporosis were developed. Results : Inadequate intake of calcium and vitamin D among the majority of women surveyed was confirmed. The highest percentage of women represented profile VIII: attitudes towards prevention of osteoporosis, characterized by insufficient exposure to sunlight and a diet deficient in both calcium and vitamin D. Conclusions: In the diets of women surveyed significant deficiencies of calcium and vitamin D were found, which confirms previous reports on the lack of nutritional support for normal women’s bone mineralization. Among the surveyed women the majority reported insufficient exposure to sunlight as a source of vitamin D additional to food. There is a need for health education of these women in the prevention of osteoporosis and especially paying attention to the proper intake of calcium and more vitamin D in their diet. At the same time, adequate exposure to the sun is vital as it is the main source of vitamin D for the body coming not from the food consumed.